Tezės 1. World Colorectal CONFERENCE - chirurgija, Lietuvos (Lietuvos chirurgija, 2013)
International Society of University Colon and Rectal Surgeons (ISUCRS) Interim meeting in Vilnius 2013 World Colorectal C O N F E R E N C E May 31 – June 1, 2013 Vilnius, Lithuania